What’s new in diagnosis and treatment of gastrointestinal diseases - Rydzewska, Grażyna (Przewodnik Lekarza/Guide for GPs, 2009)
The review summarizes selected new aspects in diagnosis and treatment of gastrointestinal diseases. New techniques including colon capsule, laser confocal endomicroscopy and disposable scopes for painless colonoscopy in diagnosis of gastrointestinal disorders are described. Progress has also been made in several areas of the treatment of gastrointestinal diseases, including biological therapy of ulcerative colitis, new indications for probiotics, use of the new antibiotic rifaximin and treatment of acute pancreatitis with continuous regional arterial infusion of proteinase inhibitor and antibiotic.